Redescription of Nerocila exocoeti Pillai, 1954 (Crustacea: Isopoda: Cymothoidae) parasitic on beloniform (Exocoetidae and Hemiramphidae) hosts with Nerocila madrasensis Ramakrishna & Ramaniah, 1978 placed into synonymy - Aneesh, Panakkool-Thamban; Helna, Ammeri Kottarathil; Valarmathi, Kandasamy; Chandra, Kailash; Mitra, Santanu (Zootaxa, 2017)
Nerocila exocoeti Pillai, 1954 is re-described based on the neotype and additional material from exocoetid hosts. Nerocila madrasensis Ramakrishna & Ramaniah, 1978 (from Madras) is placed into synonymy with N. exocoeti. Nerocila exocoeti is characterized by the presence of short coxae, postero-lateral angles of the first five pereonites not backwardly produced, pereonites 6–7 are reduced, cephalon sub-quadrate with anterior border straight; first antenna composed of eight articles and endopod of uropod half the size of exopod. Nerocila exocoeti is only known from beloniform hosts; Parexocoetus brachypterus and Exocoetus volitans (Exocoetidae); Hemiramphus sp. and Rhynchorhamphus malabaricus (Hemiramphidae) are the identified hosts for the species.